Activation of B cell apoptotic pathways in the course of Francisella tularensis infection - Zivna, Lucie; Krocova, Zuzana; Härtlova, Anetta; Kubelkova, Klara; Zakova, Jitka; Rudolf, Emil; Hrstka, Roman; Macela, Ales; Stulik, Jiri (Microbial pathogenesis, 2010)
Francisella tularensis is a facultative intracellular, gram-negative bacterium that induces apoptosis in macrophages and B cells. Here we show apoptotic pathways that are activated in the Ramos human B cell line in the course of F. tularensis infection. Live bacteria F. tularensis FSC200 activate caspases 8, 9 and 3, as well as Bid; release cytochrome c and apoptosis-inducing factor from mitochondria; and induce depolarization of mitochondrial membrane potential in the Ramos cell line, thus leading these cells to apoptosis. Unlike live bacteria, killed F. tularensis FSC200 bacteria activated only caspase 3, and did not cause apoptosis of Ramos cells as measured by annexin V. Killed bacteria also caused accumulation of anti-apoptotic protein Bclx(L) in mitochondrial membranes. Thus, live F. tularensis activates both caspase pathways (receptor-mediated and intrinsic) as well as caspase-independent mitochondrial death.
Keywords: Mitochondria; Cell Line; Caspase 3; Caspase 8; kaspasa 3; cytochromy c; protein Bid; kaspasa 9; B-lymfocyty; BH3 Interacting Domain Death Agonist Protein; lidé; Caspase 9; Humans; Cytochromes c; apoptóza; buněčné linie; membránový potenciál mitochondrií; B-Lymphocytes; kaspasa 8; Francisella tularensis; Membrane Potential, Mitochondrial; mitochondrie; Apoptosis